Reducing Blood Pressure on Elderly with Hypertension with Progressive Muscle Relaxation Therapy - Ida Noefitasari; Desi Natalia Trijayanti Idris (Journal of Ners and Midwifery, 2022)
Elderly is a process of life's journey of getting old. Physiological changes in the cardiovascular system experienced by the elderly are hypertension which occurs due to decreased elasticity of the arteries in the aging process. The purpose of this research was to analyze the effect of progressive muscle relaxation on reducing blood pressure in hypertensive elderly in Banjarejo Village. Pre-experimental research design with One group Pre-Post Test Design approach. The research sample is 30 elderly hypertension people with Quota Sampling. Research variables are progressive muscle relaxation therapy and blood pressure. Collecting data using observation sheets, using the Wilcoxon statistical test. The results showed that there were changes in blood pressure before and after therapy, namely systolic blood pressure -7.82 mmHg and diastolic blood pressure -5.54 mmHg. Wilcoxon statistical test showed p value = 0.000 which means there is a change in blood pressure in the elderly after doing progressive muscle relaxation therapy. The conclusion of this research shows that progressive muscle relaxation is a therapy that can be used to lower blood pressure in hypertensive patients.